In vitro inhibition of AKR1Cs by sulphonylureas and the structural basis. (5th October 2015) - Zhao, Yining; Zheng, Xuehua; Zhang, Hong; Zhai, Jing; Zhang, Liping; Li, Cuiyun; Zeng, Kaixin; Chen, Yunyun; Li, Qing; Hu, Xiaopeng
Abstract: Recent epidemiological studies show conflicting data for the first-line anti-diabetic sulphonylureas drugs in treating cancer progression in type II diabetes patients. How sulphonylureas promote or diminish tumor growth is not fully understood. Here, we report that seven sulphonylureas exhibit different in vitro inhibition towards AKR1Cs (AKR1C1, AKR1C2, AKR1C3), which are critical steroid hormone metabolism enzymes that are related to prostate cancer, breast cancer and endometrial diseases. Interactions of the sulphonylureas and AKR1Cs were analyzed by X-ray crystallography. Highlights: Anti-diabetes sulphonylureas drugs exhibit different in vitro inhibition towards three AKR1C enzymes. Glimepiride selectively inhibits AKR1C3, with the lowest IC 50 (0.85 μM) among the tested sulphonylureas. The structural basis of sulphonylurea inhibition of AKR1Cs is described.